Psychological Well-Being, Gender Ideology, dan Waktu sebagai Prediktor Keterlibatan Ayah - Cantyo Atindriyo Dannisworo*; Fadhilah Amalia (Jurnal Psikologi, 2019)
This study aimed to examine the role of psychological well-being, gender ideology, time spent together with children, and time spent at work in predicting father involvement. This study was conducted on fathers with at least one child aged 0-12 years old, who resided in Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek). Data was collected from 371 fathers through online questionnaires. Results from multiple regression analysis suggest that psychological well-being (β = 0.322; p < 0.01), gender ideology (β = 0.104; p < 0.05), and time spent with children (β = 0.126; p < 0.05) significantly predicted father involvement (R2 = 0.145). Time spent at work (β = 0.014) however, did not predict father involvement. Though, there are other factors that need to be considered when we are going to predict father involvement, such as father’s factors, mother’s factors, child’s factors, and contextual factors.